Evaluation of the fatigue damage behavior of fine aggregate matrices prepared with modified asphalt binders - Ng, Andressa Ka Yan (2017)
The fatigue cracking process occurs by the repeated dynamic loading from the traffic of heavy vehicle. This phenomenon initiates as microcracks and develops under two circumstances: (i) after adhesive failure, when the crack occurs at the interface aggregate-mortar, and/or (ii) after cohesive failure, when the crack develops within the mortar. Based on such interpretation of the cracking phenomenon in asphalt concrete mixtures, researchers have been using the fine aggregate matrices (FAMs) to estimate the fatigue behavior of the asphalt concrete. Good agreement is observed between the properties of the FAM and asphalt concrete properties in studies related to moisture damage, fatigue cracking and permanent deformation. Regarding the fatigue resistance of the flexible pavements, it is important to investigate the effect of the use of modified binders and the binder aging on the fatigue properties of the asphalt concrete, once that the modified binder can enhance the fatigue behavior of the asphalt concrete, and the binder aging hardens the asphalt binder and turns it into a fragile material, with negative effects on the fatigue life of the asphalt concrete. Based on these evidences, this study has the objective of evaluating the effect of modified binders and aging level on the fatigue life of the FAMs, asphalt mastics and asphalt binders. The three scales are comprised of four asphalt binders (neat, AC+PPA, AC+SBS and AC+rubber) aged in short- and long-term. The fatigue properties of the three scales were evaluated by means of the viscoelastic continuum damage (VECD) concepts, once that this theory is able to predict the asphalt concrete behavior independent of loading mode (uniaxial or torsional), control mode (stress-control or strain-control), and amplitude loading applied to induce the damage. The overall results indicate that the addition of modified binder enhances the fatigue behavior and that extended aging is capable of compromise the fatigue performance. At the scales of the binder and the mastic, the AC+rubber presented the best fatigue performance, occupying the first position in the final rank order, and the AC+SBS presented the worst performance, occupying the last position. However, at the FAM scale, the FAMs prepared with the AC+SBS presented the best fatigue performance, occupying the first position in the final rank order, and the FAMs prepared with the neat binder presented the worst behavior, occupying the last position. The best correlation between the three scales regarding the short- and long-term aging was obtained between binder and mastics aged in the PAV with the FAMs aged in long-term for 30 days.